PENGARUH LOKASI USAHA DAN PENETAPAN HARGA TERHADAP MINAT BELI PADA USAHA KONTER PULSA A&A CELL DI KOTA MAKASSAR - Tria Haryuni Dammar (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the influence of business location and pricing on purchase interest at A&A Cell Credit Counter in Makassar City. The research employed a quantitative approach with an associative design. The population consisted of 67 individuals, while the sample included 67 respondents selected through simple random sampling. Primary data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results revealed that business location has a positive and significant effect on purchase interest. Pricing was also found to have a positive and significant effect on purchase interest. Simultaneously, business location and pricing strongly influence consumers’ purchase interest. These findings emphasize that the combination of a strategic location and competitive pricing is a key factor for A&A Cell in enhancing customer attraction and loyalty amidst the intense competition in the mobile credit counter business in Makassar City.